2010
DOI: 10.5539/ijb.v2n1p35
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Estrogens Stimulate Gene Transcription in the Prolactin Promoter

Abstract: The ability of environmental estrogens to regulate gene transcription on model and physiologically complex promoter was examined in GH 3 cells, a pituitary cell line. In transient transfection studies, the pGL3 model promoter and the physiologically complex prolactin promoter were both responsive to the xenoestrogen bisphenol A and the phytoestrogen daidzein in a dose related manner. These transcriptional responses were mediated by estrogen receptors, as responses were ameliorated in the presence of ICI 180, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Jun-Xian et al ( 2013 ) used V. segetalis water extract, which had a similar effect to estrogen and PRL, and its components could bind to an estrogen receptor to activate a STAT5-signaling pathway, thereby promoting the P-STAT5 expression and milk protein synthesis. Bryant ( 2009 ) found that the PRL promoter transcription and PRL synthesis can be induced by stimulating the estrogen receptor system and pituitary transcription factor Pit-1. PRL controls the regulation of milk protein at the translational level, thereby promoting the synthesis of milk proteins.…”
Section: Pharmacological Activity Of V Segetalismentioning
confidence: 99%
“…Jun-Xian et al ( 2013 ) used V. segetalis water extract, which had a similar effect to estrogen and PRL, and its components could bind to an estrogen receptor to activate a STAT5-signaling pathway, thereby promoting the P-STAT5 expression and milk protein synthesis. Bryant ( 2009 ) found that the PRL promoter transcription and PRL synthesis can be induced by stimulating the estrogen receptor system and pituitary transcription factor Pit-1. PRL controls the regulation of milk protein at the translational level, thereby promoting the synthesis of milk proteins.…”
Section: Pharmacological Activity Of V Segetalismentioning
confidence: 99%